Insight into the key interactions of bromodomain inhibitors based on molecular docking, interaction fingerprinting, molecular dynamics and binding free energy calculation1. Issue 5 (21st May 2015) - Ran, Ting; Zhang, Zhimin; Liu, Kejun; Lu, Yi; Li, Huifang; Xu, Jinxing; Xiong, Xiao; Zhang, Yanmin; Xu, Anyang; Lu, Shuai; Liu, Haichun; Lu, Tao; et al.
<x xml:space="preserve">Abstract</x> The interaction mechanism of bromodomain inhibitors was investigated using interaction fingerprinting and binding free energy based methods.